Problems of Legal Protection of Contract and Outsourcing Workers After Law Number 6 of 2023 concerning Job Creation - Vania Andari Damanik; Zayyan Tsabitah Panjaitan; Layla Witra; Zulfikri (Jurnal Cendikia ISNU SU, 2024)
The development of an increasingly flexible labor relations system through the implementation of Fixed-Time Work Agreements (PKWT) and outsourcing after the reform of Job Creation regulations has raised a debate about the effectiveness of legal protection for workers in Indonesia. On the one hand, the policy aims to increase investment competitiveness and business efficiency, but on the other hand, it raises problems related to job security, the fulfillment of normative rights, and the balance of industrial relations. This study aims to analyze the problems of legal protection for contract and outsourcing workers in the Indonesian labor system after the reform of Job Creation regulations. This research is a normative legal research using a legislative approach and a conceptual approach. The legal materials used are primary, secondary, and tertiary legal materials that are analyzed qualitatively descriptively with a deductive conclusion method. The results of the study show that regulatory reform through Law Number 6 of 2023 provides wider flexibility on the use of PKWT and outsourcing, but has not been fully followed by the strengthening of legal protection mechanisms for workers. The elimination of restrictions on the types of work that can be outsourced, weak labor supervision, and unclear responsibilities in outsourcing employment relationships still have the potential to reduce legal certainty and the protection of workers' rights. The Constitutional Court Decision Number 27/PUU-IX/2011 remains the constitutional basis that the implementation of outsourcing must guarantee workers' rights. Therefore, the effectiveness of legal protection requires a balance between the flexibility of employment relationships, legal certainty, and the strengthening of law enforcement in the Indonesian labor system.